Determinants of Patient Loyalty in Healthcare: The Multifaceted Influence of Demographics and Nurses' Caring Behavior - Tita Rohita; Dedeng Nurkholik (Journal of Public Health and Pharmacy)
Introduction: Patient loyalty is a crucial factor in providing quality healthcare services. One effective strategy to enhance healthcare service standards is improving the caring behavior of nurses. The success of nurses in delivering caring and empathetic care can significantly influence patient loyalty, making it an essential focus for healthcare providers.